ALAT BANTU ANALISIS KERUSAKAN ANTI-FRICTION BEARING PADA UNIT ALAT BERAT - Wijayanto, Jarot (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2015)
Damage to engine part from unit of heavy equipment that often happens will interfere the activity of production because the unit of heavy equipment automatically will experience improvement. With the anticipation of anti-friction bearing demage will reduce the repair of any units of heavy equipment caused by damage to the anti-friction bearing. The purpose of creation of this tool is to help examine and analyze the damage often occurs on anti-friction bearing in unit of heavy equipment. Method of making a tool anti-friction bearing damage analysisis, on unit of heavy equipment with operating conditions approachh happens i.e. aspect of the workload and working temperature. Simulationas media tool anti-friction bearing damage can be done. The result of manufacture of tool breakage analysis of anti-friction bearing this could make it easier to know the working conditions and the variable load and speed rounds so the data parameter causes damage taken (annihilation due to the influence of vibration and haeat which occurs). Components anti-friction bearing damage analysis tool i.e. dinamo 3 phase 1500rpm, inventer, coupling flens Æ6’, shaft Æ70mmx600mm, pillow bearing Æ70mm, Housing bearing and punch, inner pack capacity 10ton, ball bearing, frame.